2020
DOI: 10.1785/0120200227
|View full text |Cite
|
Sign up to set email alerts
|

Local and Moment Magnitude Analysis in the Ridgecrest Region, California: Impact on Interevent Ground-Motion Variability

Abstract: We investigate the dependence of event-specific ground-motion residuals in the Ridgecrest region, California. We focus on the impact of using either local (ML) or moment (Mw) magnitude, for describing the source scaling of a regional ground-motion model. To analyze homogeneous Mw, we compute the source spectra of about 2000 earthquakes in the magnitude range 2.5–7.1, by performing a nonparametric spectral decomposition. Seismic moments and corner frequencies are derived from the best-fit ω−2 source models, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 81 publications
(85 reference statements)
3
13
0
Order By: Relevance
“…Priors for the corner frequency f c of each event depend on the event size but are assumed to follow a lognormal distribution derived from a corresponding stress drop prior with a median stress drop of 5 MPa and standard deviation of 0.4 in log10 units. These values are in line with recent work(Baltay et al, 2013;Bindi, Zaccarelli, & Kotha, 2020;…”
supporting
confidence: 93%
“…Priors for the corner frequency f c of each event depend on the event size but are assumed to follow a lognormal distribution derived from a corresponding stress drop prior with a median stress drop of 5 MPa and standard deviation of 0.4 in log10 units. These values are in line with recent work(Baltay et al, 2013;Bindi, Zaccarelli, & Kotha, 2020;…”
supporting
confidence: 93%
“…They too should be considered potentially biased in the same manner as the spectral decomposition analyses. For example, at Ridgecrest Bindi, Zaccarelli, et al (2020) obtained a similar apparent depth dependence to stress drop as Trugman (2020) and also did not explicitly consider an increase in Q with source depth. Bindi et al (2021) performed a subsequent study and identified a combination of depth and distance varying attenuation and stress drop increasing with depth that were able to fit the observed spectra.…”
Section: Implications For Depth Dependence Of Earthquake Stress Dropmentioning
confidence: 99%
“…Parker et al (2020) investigated the performance of ground motion prediction equations on the aftershocks of the 2019 Ridgecrest earthquake and observed that the deeper earthquakes exhibited higher ground acceleration, consistent with their having higher stress drop. Like the studies by Trugman (2020) and Bindi, Zaccarelli, et al (2020) of the same sequence, they did not include any dependence of attenuation on source depth in their analysis. In empirical ground motion prediction, it is not essential to distinguish whether source or path effects cause a trend when interpolating within a data set, but it is required to extrapolate predictions to different regions, or larger magnitude earthquakes (e.g., Bommer et al, 2007).…”
Section: Implications For Depth Dependence Of Earthquake Stress Dropmentioning
confidence: 99%
“…They also showed that the frequency range of the Southern California regional seismic network data is insufficient to resolve source scaling and absolute values of stress drop, and their variation, independently. This limitation is supported by the contrasting results of Trugman (2020), Bindi, Zaccarelli, and Kotha (2020), Bindi et al. (2021), and Abercrombie et al.…”
Section: Introductionmentioning
confidence: 94%
“…They also showed that the frequency range of the Southern California regional seismic network data is insufficient to resolve source scaling and absolute values of stress drop, and their variation, independently. This limitation is supported by the contrasting results of Trugman (2020), Bindi, Zaccarelli, and Kotha (2020), Bindi et al (2021), and Abercrombie et al (2021) for aftershocks of the 2019 Ridgecrest, California earthquake. Shearer and Abercrombie (2021) combined surface network with high-frequency deep borehole recordings to resolve the ambiguity near Cajon Pass.…”
mentioning
confidence: 99%